2008
DOI: 10.1007/s00198-008-0770-4
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral fractures in patients with chronic obstructive pulmonary disease: the EOLO Study

Abstract: In COPD patients the risk of vertebral fractures is strictly related to the severity of the disease. The use of glucocorticoids and reduced QUS at calcaneous may represent additional risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 41 publications
10
80
0
2
Order By: Relevance
“….One plausible explanation for the relatively young menopausal age of some of the study subjects is the effect of smoking itself in reducing sex steroids. (55) In additional to more years since menopause, the group with COPD who fractured had lower BMIs, a finding reported previously, (10) and lower levels of 25(OH)D when compared with the group that did not fracture. These findings suggest that besides the pulmonary disease, COPD patients experience other risk factors for fracture, and probably each of these contributes to a decrease in bone strength.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“….One plausible explanation for the relatively young menopausal age of some of the study subjects is the effect of smoking itself in reducing sex steroids. (55) In additional to more years since menopause, the group with COPD who fractured had lower BMIs, a finding reported previously, (10) and lower levels of 25(OH)D when compared with the group that did not fracture. These findings suggest that besides the pulmonary disease, COPD patients experience other risk factors for fracture, and probably each of these contributes to a decrease in bone strength.…”
Section: Discussionsupporting
confidence: 49%
“…Fifty-four subjects were excluded because of the following: oral glucocorticoid use > 3 months (20), other secondary causes of osteoporosis (12), declined to participate (8), nonsmoking COPD (3), age > 75 years (10), and allergy to tetracycline (1). The remaining 39 COPD patients were selected to have BMD and blood tests.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuti et al 21 reported that COPD duration was 1 year in 13.1%, 1-5 years in 31.2% and above 5 years in 55.8% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…All the collected data were compiled and analyzed using the SPSS (Statistical package for social science) 21 In this study bone mineral density was normal in 6 (10.0%), osteopenia in 24 (40.0%) and osteoporosis in 30 (50%) patients as regards BMD in femoral neck; while normal bone mineral density was in 4 (6.7%), osteopenia in 17 (28.3%) and osteoporosis in 39 (65.0%) patients as regards BMD in lumbar spine. Also it was demonstrated that 90% of patients with COPD varying from moderate to very severe had abnormal BMD in femoral neck and about 93% of patients with COPD varying from moderate to very severe had abnormal BMD in lumbar spine.…”
Section: Methodsmentioning
confidence: 99%